Measuring Risk Aversion Behavior Using Szpiros Approach: Case Study in Indonesias Life Insurance Industry - Kristio Rapi; Dominicus Savio Priyarsono; Siti Jahroh; Toni Bakhtiar (Persatuan Aktuaris Indonesia, 2026)
Life insurance industry shows promising benefits for Indonesia's economic and social sector, yet its penetration continues to decrease since 2016 despite income growth. This study addresses the phenomenon by analyzing the risk preference of Indonesian consumers using Szpiro's approach to measure risk aversion, then analyzes the effect of risk aversion on life insurance demand in Indonesia. We use data from Indonesia Insurance Statistics from 2006 to 2022 with annual period. Stationarity tests were conducted before time series estimation, Ordinary Least Square is used to estimate time series data, and Klein's rule is used to address multicollinearity problem in regression analysis. Evidence is presented in support of the positive effect of risk aversion on life insurance demand. The degree of relative risk aversion in Indonesia is estimated at 0.0915 with risk aversion value in 2022 of 0.1402, indicating that Indonesian people is a risk-averse individuals. Therefore, given the fact that Indonesia is a non-high-income country with risk-averse consumers, the opportunity to enhance life insurance demand remains open. This finding will help insurers in demand and pricing analysis.